2007
DOI: 10.1159/000106577
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Photodynamic Therapy

Abstract: Background: Photodynamic therapy (PDT) is increasingly used in the treatment of various skin diseases. The main adverse effect in PDT treatment is pain. Each lesion is generally treated twice, and clinical experience suggests that the 2nd treatment causes more pain than the 1st and thus becomes a therapy-limiting factor. Objectives: To investigate the intrapatient variation in the experience of pain, between 1st and 2nd PDT treatments. Methods: We registered patients treated with PDT by using a mechanical visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 16 publications
8
33
3
4
Order By: Relevance
“…Even though it was not observed in a vast number of our patients, a few did report very strong discomfort during illumination. It has been shown previously that the intensity of pain significantly increased at the second PDT treatment [14]. We also observed an increase in pain with the number of PDT sessions.…”
Section: Discussionsupporting
confidence: 80%
“…Even though it was not observed in a vast number of our patients, a few did report very strong discomfort during illumination. It has been shown previously that the intensity of pain significantly increased at the second PDT treatment [14]. We also observed an increase in pain with the number of PDT sessions.…”
Section: Discussionsupporting
confidence: 80%
“…In summary, both types of lamps achieved comparable results in terms of efficacy, while fewer side effects such as local pain were observed with wIRA. Furthermore, studies revealed that the intensity of pain during PDT correlated more often with the size of the treated area than with the dose of light used [12, 13]. We conclude that the novel treatment regime for cutaneous sarcoidosis introduced here clearly shows that methyl aminolevulinate (Metvix) as well as wIRA represent useful alternative therapeutic tools to optimize treatment of cutaneous sarcoidosis with PDT.…”
Section: Discussionmentioning
confidence: 88%
“…Our patients experienced mild pain during the irradiation. The reason for this moderate sensation might be the sites of the treated lesions, known to be generally associated with less pain (arms, limbs or trunk compared with the face or scalp) and likely the smaller amount of cells in the GA lesions that actively metabolized MAL into the photo-active protoporphyrin IX compared with actinic keratosis or basal cell carcinoma [12, 13]. …”
Section: Discussionmentioning
confidence: 99%